2019
DOI: 10.1016/j.ejca.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Membrane human equilibrative nucleoside transporter 1 is associated with a high proliferation rate and worse survival in resected intrahepatic cholangiocarcinoma patients not receiving adjuvant treatments

Abstract: Human equilibrative nucleoside transporter 1 (hENT-1) is a membrane nucleoside transporter mediating the intracellular uptake of nucleosides and their analogues. hENT-1 was recently reported to have a predictive role in intrahepatic cholangiocarcinoma (iCC) patients receiving adjuvant gemcitabine-based chemotherapy, but its biological and clinical significance in iCC remains unsettled. This study investigated the role of hENT-1 in regulating tumour growth and predicting the survival of 40 resected iCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Therefore, the present results suggest that hENT1 and dCK function not only as feasible, but also useful prognostic markers in the routine diagnosis of meningiomas when combined with the WHO grading system. Consistent with the present results, the significance of hENT1 as a prognostic marker has already been demonstrated in intrahepatic cholangiocarcinoma, 33 ampullary carcinoma, 38 and gastric cancer. 39 Similarly, a relationship between high dCK expression levels and a poor prognosis has been reported in esophageal cancer, 40 breast cancer, 41 and adenocarcinoma of the esophagus, esophagogastric junction, and gastric cardia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the present results suggest that hENT1 and dCK function not only as feasible, but also useful prognostic markers in the routine diagnosis of meningiomas when combined with the WHO grading system. Consistent with the present results, the significance of hENT1 as a prognostic marker has already been demonstrated in intrahepatic cholangiocarcinoma, 33 ampullary carcinoma, 38 and gastric cancer. 39 Similarly, a relationship between high dCK expression levels and a poor prognosis has been reported in esophageal cancer, 40 breast cancer, 41 and adenocarcinoma of the esophagus, esophagogastric junction, and gastric cardia.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, high hENT1 expression levels were associated with a high Ki-67 labeling index and shorter overall survival in intrahepatic cholangiocarcinomas treated without gemcitabine. 33 The present results are consistent with these findings and collectively suggest that the growth regulatory role of hENT1 is a feature shared by some types of cancer cells instead of being unique to meningioma cells. Although the mechanisms underlying the growth regulatory function of hENT1 remain speculative and hypothetical, hENT1 may promote the proliferative activity of tumor cells through an adequate supply of precursors for DNA synthesis based on the primary function of hENT1 as a transporter of nucleosides and nucleobases, which are precursors of nucleotides that are essential for DNA synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, high expression levels of hENT-1 emerged as a prognostic biomarker of poor outcome in cholangiocarcinoma. Indeed, while a first study showed a significant association between disease-free survival (DFS) and high expression of membrane hENT-1 in gemcitabine-treated patients [53,54], hENT-1 overexpression was associated to high proliferation rate and significantly shorter survival in resected intrahepatic cholangiocarcinoma patients who did not receive adjuvant treatments [55]. This might be explained by the different levels of hENT-1 expression and proliferative rates in different tumor types and warrants further, larger studies.…”
Section: Role Of Hent-1 In Gemcitabine Activity As Potential Predictive Biomarkermentioning
confidence: 99%
“…Among the family of nucleoside transporters, ENT1 is the most widely expressed and highly selective transporter of purines and pyrimidine nucleosides [ 30 ]. Some studies have reported that ENT1 could be used as a bona fide target for potential drugs related to cancer therapy [ 31 34 ]. Our group found that ENT1 is overexpressed on choriocarcinoma cells (JEG-3 cells) by analyzing the expression of transporters.…”
Section: Introductionmentioning
confidence: 99%